Modern aspects of the prevalence and clinical picture of rosacea - E. E. Zhiltsova; K. V. Mezhevaya; S. A. Isakov (Лечащий Врач)
This article discusses in detail the prevalence of rosacea among the population, the percentage and quantity of morbidity depending on sex, race and skin phototype, the clinical picture of four subtypes and one variant of rosacea. Rosacea is a topical problem due to the variety of clinical forms and the lack of clear data on the etiology. The presence of cosmetic defects exacerbates the emotional state of the patients.